2020
DOI: 10.15252/embr.201949886
|View full text |Cite
|
Sign up to set email alerts
|

Key phosphorylation sites in GPCR s orchestrate the contribution of β‐Arrestin 1 in ERK 1/2 activation

Abstract: β‐arrestins (βarrs) are key regulators of G protein‐coupled receptor (GPCR) signaling and trafficking, and their knockdown typically leads to a decrease in agonist‐induced ERK1/2 MAP kinase activation. Interestingly, for some GPCRs, knockdown of βarr1 augments agonist‐induced ERK1/2 phosphorylation although a mechanistic basis for this intriguing phenomenon is unclear. Here, we use selected GPCRs to explore a possible correlation between the spatial positioning of receptor phosphorylation sites and the contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 65 publications
4
62
0
Order By: Relevance
“…Although it is tempting to speculate that some of these biosensors could provide evidence for arrestin activation without arrestin C-tail displacement, such inferences are notoriously difficult to make for biosensors. Recently, the biosensor experiments were corroborated by a study using an intracellularly expressed antibody fragment (intrabody) specific for active arrestin-2 (Baidya et al, 2020). The binding of the intrabody to arrestin-2 was triggered by ligand stimulation of the V 2 vasopressin receptor, but not by the B 2 bradykinin receptor, although both recruited arrestin-2 to a similar extent.…”
Section: Arrestin Activation Without Triggering Internalizationmentioning
confidence: 92%
“…Although it is tempting to speculate that some of these biosensors could provide evidence for arrestin activation without arrestin C-tail displacement, such inferences are notoriously difficult to make for biosensors. Recently, the biosensor experiments were corroborated by a study using an intracellularly expressed antibody fragment (intrabody) specific for active arrestin-2 (Baidya et al, 2020). The binding of the intrabody to arrestin-2 was triggered by ligand stimulation of the V 2 vasopressin receptor, but not by the B 2 bradykinin receptor, although both recruited arrestin-2 to a similar extent.…”
Section: Arrestin Activation Without Triggering Internalizationmentioning
confidence: 92%
“…This coordinated action of different GRKs would be translated into distinct biological outcomes upon phosphorylation barcoding [ 42 , 43 , 44 ], which is envisioned as a general signalling hub that would be biased by the conformation of the receptor notably induced by the binding of arrestins and cellular effectors, the nature of the chemokine ligand ( Figure 1 b) and the possible allosteric interactions with other receptors (i.e., oligomerization, Figure 1 c), including atypical chemokine receptors, which are known for their regulatory effect on chemoattractant signals. Functional evidence for this concept of phosphorylation barcoding was provided by recent studies revealing that switching the code pattern of phosphosites between GPCRs reprograms arrestin activation [ 45 , 46 ].…”
Section: Roles Of Grks In Regulating Chemokine Receptor Activationmentioning
confidence: 99%
“…Function-based evidence and recent structure-based evidence have suggested that patterns of receptor phosphorylation ("barcodes") may be a critical determinant of b-arrestin action. In this issue of EMBO Reports, Baidya and colleagues (Baidya et al, 2020a) report that specific receptor phosphorylation site clusters ("codes") determine whether b-arrestin 1 acts to promote or inhibit receptor activation of Erk mitogen-activated protein kinases. They provide direct evidence for a functional barcode system by transferring inhibitory and stimulatory codes between receptors, suggesting future work to understand just how code site location in a receptor and its phosphorylation status can lead to very different functions of bound b-arrestin proteins.…”
mentioning
confidence: 99%
“…The authors also make use of an intrabody as a sensor to label a b-Arr1 active conformation after activation of their mutant receptors, which demonstrates a shift in b-Arr1 active conformation upon switching phosphocodes (Baidya et al, 2020a). A recent study by the same authors highlights the need for additional such sensors that detect further distinct active conformations (Baidya et al, 2020b).…”
mentioning
confidence: 99%
See 1 more Smart Citation